2008
DOI: 10.1542/peds.2008-0458
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Highly Endemic Multiply Antibiotic-Resistant Shigellosis in Children in the Peruvian Amazon

Abstract: OBJECTIVE Our goal was to estimate the impact of a Shigella vaccine in an area where shigellosis is endemic by characterizing the disease burden and antibiotic-resistance profiles of isolates and by determining the prevalence of Shigella flexneri serotypes. PATIENTS AND METHODS We conducted a 43-month-long prospective, community-based diarrheal disease surveillance in 442 children <72 months of age in the Peruvian Amazon between October 1, 2002, and April 15, 2006. RESULTS The incidence of diarrheal diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
81
0
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 26 publications
11
81
0
12
Order By: Relevance
“…22 A few studies have assessed risk factors for diarrhea by enteric pathogens. In Kosek and others, 9 age, maternal education, floor type, and rainy season were found to be significant risk factors for shigellosis in children 5 years of age. For Campylobacter, maternal education and household water connection were found to be significant risk factors for this age group.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…22 A few studies have assessed risk factors for diarrhea by enteric pathogens. In Kosek and others, 9 age, maternal education, floor type, and rainy season were found to be significant risk factors for shigellosis in children 5 years of age. For Campylobacter, maternal education and household water connection were found to be significant risk factors for this age group.…”
Section: Introductionmentioning
confidence: 79%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies have identified lack of caregiver handwashing with soap and drinking water treatment, poor water storage practices, and lack of caregiver knowledge of diarrhea prevention as important risk factors for diarrheal disease in pediatric populations. [2][3][4][5][6][7][8] Water, sanitation, and hygiene (WASH) interventions promoting household chlorination of drinking water and handwashing with soap have the potential to reduce diarrheal disease incidence in children less than 5 years of age by an estimated rate of 20-40%. [9][10][11] However, in many low-income countries, community-based WASH interventions are often difficult to implement in urban settings because of limited community health work infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…incluye la ampicilina, el trimetoprim-sulfametoxazol y el ácido nalidíxico, pero debido al aumento a nivel mundial de la resistencia de Shigella spp. a la mayoría de estos antibióticos (6), se recomienda la ciprofloxacina como el medicamento de elección para pacientes con shigelosis de cualquier grupo de edad (7,8).…”
unclassified